Etiology, Clinical Manifestations, and Imaging Evaluation of Intestinal Obstruction in Adults at Tertiary Hospital in Mogadishu, Somalia: A Retrospective Study [Letter] - Indiran V (International Journal of General Medicine)
Venkatraman Indiran Department of Radiodiagnosis, Sree Balaji Medical College and Hospital, Chennai, TamilnaduCorrespondence: Venkatraman Indiran, Department of Radiodiagnosis, Sree Balaji Medical College and Hospital, 7 Works Road, Chromepet, Chennai, Tamilnadu, 600044, India, Tel +91 044 22653429 ; +91 9443067358, Email ivraman31@gmail.com